1998
DOI: 10.1007/s003840050146
|View full text |Cite
|
Sign up to set email alerts
|

Rhomboid flap procedure for pilonidal sinus: results from 67 cases

Abstract: Sixty-seven patients with chronic pilonidal sinuses were treated by excision and rhomboid flap transposition (RFT). Primary healing was obtained in all patients except two who developed a seroma and one who had a partial dehiscence of the surgical wound due to a hematoma, which necessitated drainage through the margin of the flap. The average stay was 5.3 days (range 1-16). All patients returned to normal activities within 2 weeks of surgery. No late recurrence occurred after a mean follow-up of 74.4 months (r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
5

Year Published

2003
2003
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(38 citation statements)
references
References 11 publications
0
33
0
5
Order By: Relevance
“…All patient returned to their normal activities in 8 to 14 days post operatively. [14][15][16] Surgery should not only eradicate the existing sinus and crevice in which the hair tends to accumulate but also aim to establish complete and rapid primary healing and to prevent recurrence. 17,18 The ideal treatment of PNS remains a topic of debate.…”
Section: Resultsmentioning
confidence: 99%
“…All patient returned to their normal activities in 8 to 14 days post operatively. [14][15][16] Surgery should not only eradicate the existing sinus and crevice in which the hair tends to accumulate but also aim to establish complete and rapid primary healing and to prevent recurrence. 17,18 The ideal treatment of PNS remains a topic of debate.…”
Section: Resultsmentioning
confidence: 99%
“…3 These include conservative nonexcisional care, 4 phenol injection, [5][6][7][8] pit excision and tract brushing (Millar-Lord procedure), 9,10 Bascom procedure, [11][12][13] excision and leaving the wound to granulate, [14][15][16][17] excision and marsupialisation, 17,18 excision and primary closure with mid-line or asymmetric incisions, [14][15][16][17][18][19][20] or excision and closure using local flaps. The latter include Karydakis procedure, [21][22][23][24] Romboid and Limberg flaps, [25][26][27][28] Z-plasty, [29][30][31] and V-Y flaps, [32][33][34][35] or other reconstructions. [36][37][38] Each method has its own advocates.…”
Section: Discussionmentioning
confidence: 99%
“…Techniques, which flatten the natal cleft or avoid a mid-line scar [21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] are reported to have fewer recurrences. 2,[21][22][23][24][25][26][27][28][29][30][31][32][33][34][35] In this study, we used a new, simple technique to flatten the natal cleft, namely the division of the coccycutaneous attachments. 1 This has resulted in elevation of the skin of the lower angle of the wound, 2c m on average, without any untoward effects.…”
Section: Complication Patients (N)mentioning
confidence: 99%
“…Today the most common plasty methods are Limberg flap, V-Y plasty, and Z plasty. In the literature, wound infection, wound separation and seroma rates after V-Y plasty are reported respectively as: 0-10.2%, 0-10.2% and 0-4.6% (Schoeller et al, 1997;Milito et al, 1998;Nursal et al, 2010). In a study including 353 cases operated with Limberg flap, the recurrence rate is reported as 3.1%, and infection rate as 6.5% (Mentes et al, 2008).…”
Section: Plastiesmentioning
confidence: 99%